2021
DOI: 10.3390/hydrology8040179
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in Sub-Catchment Fractional Snowpack and Snowmelt Parameterizations and Hydrologic Modeling for Climate Change Assessments in the Western Himalayas

Abstract: The present work proposes to improve estimates of snowpack and snowmelt and their assessment in the steep Himalayan ranges at the sub-catchment scale. Temporal variability of streamflow and the associated distribution of accumulated snow in catchments with glacier presence in the Himalayas illustrates how changes in snowpack and snowmelt can affect the water supply for local water management. The primary objective of this study is to assess the role of elevation, temperature lapse rate (TLR), and precipitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…ydrology 2022, 9, x FOR PEER REVIEW 13 of 2 also indicates the reliability of the streamflow simulations. Calibration efficiency indice were similar to efforts using monthly rain gauge-based data for SWAT [24,28,78] and ra dar-based simulations [22,23,26,79,80]; however, the validation efficiency indices wer higher than those for calibration. NSE and RSR metrics for calibration were 0.58 and 0.65 respectively; for validation, the values were 0.92 and 0.28, respectively.…”
Section: Sensitivity Analysis and Model Calibrationsupporting
confidence: 60%
“…ydrology 2022, 9, x FOR PEER REVIEW 13 of 2 also indicates the reliability of the streamflow simulations. Calibration efficiency indice were similar to efforts using monthly rain gauge-based data for SWAT [24,28,78] and ra dar-based simulations [22,23,26,79,80]; however, the validation efficiency indices wer higher than those for calibration. NSE and RSR metrics for calibration were 0.58 and 0.65 respectively; for validation, the values were 0.92 and 0.28, respectively.…”
Section: Sensitivity Analysis and Model Calibrationsupporting
confidence: 60%
“…For the computation of snow cover, snowmelt and glacier melt, SPHY works based on the degree‐day approach using temperature index model (Terink et al, 2015). Many studies related to cryospheric applications have shown the applicability of temperature index model using degree‐day factor (DDF) in the modelling of snowmelt and glacier melt across world that follows an empirical relationship between melt rate and air temperature (Singh, Jain, & Goyal, 2021; Singh & Muñoz‐Arriola, 2021). In SPHY model, the snow–glacier induced and other Q components namely, glacier Q , snow Q , rain Q , base Q and total Q are computed at each grid scale and their contribution can be accounted at subbasin scale or at a desired outlet, separately.…”
Section: Methodsmentioning
confidence: 99%
“…In Himalaya, along with glaciers, snow is equally important in the context of natural hazards, such as avalanche mitigation, flood predictions, and so forth (Bolch et al, 2012). In few studies, climate variations have shown a strong influence on the seasonal distribution of snow cover, which has negatively impacted the snowmelt runoff and glacier mass balances (Singh, Jain, & Goyal, 2021; Singh & Muñoz‐Arriola, 2021). Based on various topographical and weather parameters such as elevation level and temperature variations, the Himalayan climatology can be distributed into three zones namely, upper zones, middle and lower (Sood et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation